Junior High Career Planning: What Students Want - Bardick, Angela D.; Bernes, Kerry B.; Magnusson, Kris C.; Witko, Kim D. (Canadian Journal of Counselling and Psychotherapy, 2007)
This research used The Comprehensive Career Needs Survey to assess the career counselling needs of 3,562 junior high students in Southern Alberta. This article examines junior high students' responses regarding their perceptions of (a) the relevance of career planning, (b) who they would approach for help with career planning, and (c) what help they would like during the career planning process. Results indicate career planning is important to junior high students; they are most likely to rely on parents and friends rather than teachers or counsellors for help with career planning; and they would like help with career decision making, obtaining relevant information and support, and choosing appropriate courses. Implications for teachers, school counsellors, parents, and community services are discussed.